2011
DOI: 10.1557/opl.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Group IV Nanocrystals for Silicon Photovoltaics

Abstract: Silicon nanocrystals (nc-Si), have been shown to act as opto-electronic centers enabling light emission by carrier recombination, when precipitated in a silicon nitride (Si3N4) host. In this work, nc-Si and Germanium nanocrystals (nc-Ge) are studied in sputtered films of Si3N4 and SiGeN for application as tandem cell layers in a Si solar cell. The samples are annealed in a nitrogen gas and forming gas ambient, from 500 ºC to 900 ºC, to investigate the influence of temperature on photoluminescence and photocond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Elsewhere, similar PL bands were attributed to Si/Ge‐related defects . In further studies, no PL bands are observed, neither in the visible nor the infrared region.…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 58%
See 3 more Smart Citations
“…Elsewhere, similar PL bands were attributed to Si/Ge‐related defects . In further studies, no PL bands are observed, neither in the visible nor the infrared region.…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 58%
“…Ge‐rich Si 3 N 4 films (GeSiN x ) were synthesized by MS Ge‐ion implantation and CVD . The annealing step to form the Ge nanocrystals is usually performed between 700 and 1000 °C.…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 99%
See 2 more Smart Citations